The Use of Oral Presentation Techniques to Improve Communication Skills in Social Studies Learning - I Ketut Suardika; La Ode Safiun Arihi; Ali Hadara; Hasniah Hasniah; Tri Zahra Ningsih (Ta'dib, 2023)
Communication skills play a crucial role in IPS (Social Studies) education, but often they are not fully developed due to the lack of suitable teaching methods. Therefore, this study aimed to explore the effectiveness of using oral presentations as a teaching strategy to enhance communication skills among junior high school students. The study utilized an experimental research design with a pretest-posttest control group. Sixty students were divided into two groups: the control group and the experimental group. The data were collected using an observation sheet to assess students' communication skills, and the data analysis employed the t-test. The findings demonstrated that the oral presentation technique had a significant impact on improving the communication skills of junior high school students in IPS learning. This was supported by a t-test value of 0.000 (below 0.05). Based on these results, the author concluded that employing oral presentations as a teaching strategy is effective in enhancing the communication skills of junior high school students in IPS education. These research findings carry important implications for educators, students, and stakeholders as they recognize and prioritize the development of communication skills in IPS learning.